Peran Nilai Positif Pekerjaan-Keluarga sebagai Mediasi Pengaruh Dukungan Suami terhadap Kepuasan Kerja dan Kepuasan Perkawinan pada Perempuan yang Bekerja - Triana Noor Edwina Dewayani Soeharto; - Faturochman; MG. Adiyanti (Faculty of Psychology, Universitas Gadjah Mada, 2013)
The purpose of this study is to examine the role of work-family positive value, which is based on gender theory and ecological theory, as a mediation of the influence of husband’s support toward both job and marital satisfaction among working women. The subjects of this study were 188 female workers who lived together with their husbands and took care of children below 12 years. By applying structural equation modeling, the proposed model fit with the data (χ2 = 1,628; p=0.202 and GFI = 0.996). Furthermore, the result shows that the effect of variabel of husband’s support increases when the work-family positive value as a mediating variable is applied. The theoretical and practical implications of the result are discussed. Keywords: husband’s support, work-family positive value, job satisfaction, marital satisfaction